Comparative Analysis of Judicial Authority in Upholding Constitutionality: Indonesia’s Constitutional Court and us Supreme Court - Wasiska, Asti; Saragih, Geofani Milthree; Setyawan, Edy; Tarmudi, Tarmudi (Jurnal Pembaharuan Hukum, 2025)
In democratic governance, the Indonesian Constitutional Court and the United States Supreme Court serve as constitutional guardians, exercising judicial review within their respective legal traditions to uphold checks and balances and ensure the supremacy of the constitution. This study aims to compare the roles of the Indonesian Constitutional Court and the United States Supreme Court in implementing the principle of checks and balances through the judicial review mechanism. Using a normative juridical approach and comparative law methods, this study examines the institutional structure, scope of authority, and constitutional impact of the decisions of both institutions. The primary data sources include the constitutions of each country, specifically Article 24C of the 1945 Constitution and Article III of the United States Constitution, as well as Law Number 24 of 2003 concerning the Constitutional Court (in conjunction with Law Number 8 of 2011). The study shows that the United States Supreme Court has broader interpretive authority due to its common law tradition and the power of precedent, while the Indonesian Constitutional Court has limited authority within the context of a more normative civil law system. Differences in legal systems and institutional design affect the effectiveness of their oversight function.